To find the zeros of the quadratic function \(y = x^2 + 15x + 36\), we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In our case, the coefficients are:
- \(a = 1\)
- \(b = 15\)
- \(c = 36\)
We first need to compute the discriminant \((b^2 - 4ac)\):
\[ b^2 - 4ac = 15^2 - 4 \cdot 1 \cdot 36 = 225 - 144 = 81 \]
Now we can substitute the values into the quadratic formula:
\[ x = \frac{-15 \pm \sqrt{81}}{2 \cdot 1} \]
Since \(\sqrt{81} = 9\), we have:
\[ x = \frac{-15 \pm 9}{2} \]
This gives us two possible solutions:
- For \(x = \frac{-15 + 9}{2}\):
\[ x = \frac{-6}{2} = -3 \]
- For \(x = \frac{-15 - 9}{2}\):
\[ x = \frac{-24}{2} = -12 \]
Thus, the zeros of the quadratic function are:
- Smaller zero: \(x = -12\)
- Greater zero: \(x = -3\)
To summarize:
smaller zero: \(x = -12\) ; greater zero: \(x = -3\)